SPECIFICS OF REAL RIGHTS IN THE SPHERE OF MERCHANT SHIPPING - Ochkurenko, Sergey; Vasiliev, Stanislav; Zenin, Sergey; Koval, Vladimir (Revista Inclusiones, 2020)
The article studies the specifics of real rights in the sphere of merchant shipping. This paper aims at determining the typical features of real rights to material objects of merchant shipping. The authors of the article use the systemic-structural method to determine the role of ownership and other property rights in the legal regulation of merchant shipping relations. The logical-semantic method is utilized to examine civil laws and international conventions. The article concludes that property rights lay the foundations for the subsequent regulation of obligations and even public relations. However, liability law and public law cannot regulate property relations but can have a certain impact on them. This also applies to limited real rights that arise in connection with the lease of a vessel (in particular, a bareboat charter) or during the marine transportation of commercial and noncommercial cargo.